C-Reactive Protein at 24 Hours after Hospital Admission may have Relevant Prognostic Accuracy in Acute Pancreatitis: A Retrospective Cohort Study - Cardoso,Filipe S (2015)
Introduction: C-reactive protein (CRP) and Bedside Index for Severity in Acute Pancreatitis (BISAP) have been used in early risk assessment of patients with AP. Objectives: We evaluated prognostic accuracy of CRP at 24 hours after hospital admission (CRP24) for in-hospital mortality (IM) in AP individually and with BISAP. Materials and Methods: This retrospective cohort study included 134 patients with AP from a Portuguese hospital in 2009-2010. Prognostic accuracy assessment used area under receiver-operating characteristic curve (AUC), continuous net reclassification improvement (NRI), and integrated discrimination improvement (IDI). Results: Thirteen percent of patients had severe AP, 26% developed pancreatic necrosis, and 7% died during index hospital stay. AUCs for CRP24 and BISAP individually were 0.80 (95% confidence interval (CI) 0.65-0.95) and 0.77 (95% CI 0.59-0.95), respectively. No patients with CRP24 <60 mg/l died (P = 0.027; negative predictive value 100% (95% CI 92.3-100%)). AUC for BISAP plus CRP24 was 0.81 (95% CI 0.65-0.97). Change in NRInonevents (42.4%; 95% CI, 24.9-59.9%) resulted in positive overall NRI (31.3%; 95% CI, −36.4% to 98.9%), but IDInonevents was negligible (0.004; 95% CI, −0.007 to 0.014). Conclusions: CRP24 revealed good prognostic accuracy for IM in AP; its main role may be the selection of lowest risk patients.